Comparison of ACI-318 and TS-500 codes for nonlinear seismic analysis of RC structures using force-based fiber element approach - Karaton, Muhammet; Osmanli, Omer Faruk; Awla, Halmat Ahmed (Elsevier Science Inc, 2023)
The material properties such as compressive strength, tensile strength, and modulus of elasticity have been significant phenomena in the nonlinear seismic analysis of RC structures. In several national codes, different equations for the material properties of concrete based on compressive strength are suggested. The effectiveness of these equations in the analysis of RC structures should be investigated to determine the seismic response of the structure. In this study, the effectiveness of ACI-318 and TS 500 design codes is investigated in the numerical modeling of RC structures. For this purpose, the seismic responses of two RC structures experimented in the laboratory are used. The first structure is a two-dimensional three-bay and four-story RC bare frame structure that was tested in European Laboratory for Structural Assessment. The second structure is an RC tall bridge pier that was tested at Pacific Earthquake Engineering Research Center. The numerical solutions are obtained by using the Force-based Fiber Element Approach. The experimental and numerical analysis results are compared in terms of top displacements and damage zones. The concrete material properties which provide the best approximation to the experimental results are investigated for both design codes. It is concluded that the material properties of RC structures determined according to the ACI-318 code can be used for the Force-based Fiber Element Approach with regard to displacement response and damage regions.
Keywords: Reinforced concrete; Nonlinear seismic analysis; Force-based fiber element approach; Top displacement; And damage zone